2004
DOI: 10.1079/phn2003593
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and obesity in adolescent Tehrani students, 2000–2001: an epidemic health problem

Abstract: Objective: Overweight has become a public health problem in most developing countries. Evidence suggests that adolescence is a critical period in determining adulthood obesity and its complications. The present study was carried out to assess the prevalence of overweight and obesity among secondary school students. Design and setting: This descriptive study was conducted in Tehran city, 2000-2001. Body weight and height were measured and body mass index (BMI) values were calculated. Underweight, overweight and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
69
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 8 publications
11
69
4
Order By: Relevance
“…The Open Obesity Journal, 2009, Volume 1 13 globe also showed that female gender are at risk of being overweight and obese [15][16][17].…”
Section: Obesity Levels In Urban Indian Childrenmentioning
confidence: 99%
“…The Open Obesity Journal, 2009, Volume 1 13 globe also showed that female gender are at risk of being overweight and obese [15][16][17].…”
Section: Obesity Levels In Urban Indian Childrenmentioning
confidence: 99%
“…The significant prevalence of overweight in Iran [12][13][14] necessitates studying different aspects of dietary habits, especially among adolescents. Appropriate public measures can then be designed according to any deviations from optimal eating practices.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, there has been an alarming rise in obesity in the developed world (5,6) and, increasingly, in the developing world as well (7)(8)(9). The obesity rate in the United States doubled between 1970 and 2000, to almost 30% (5); worldwide, nearly 1.5 billion people are now overweight or obese (9).…”
mentioning
confidence: 99%